A review on pollination study of Parkia- An economically and ecologically important genus of food tree species - Phukan Borpuzari, Papori; Singh, Manish Kumar (Indian Journal of Agroforestry, 2022)
The higher rate of effective pollination increases fruit production where investigation of pollination efficiency of different pollinators is most important. Which is affects global biodiversity loss and ultimate declines on plant reproduction. Available old literature on principal pollinators of Asian Parkia, assumed to be pollinated by bats (chiropterophilous) and the process is peculiar to species growing in tropical regions where suitable vegetarian bats occur. During January 2019 author experienced in the West Tripura village, where more than 100s of bats were hung available on P. timoriana tree in day time. As discussed with the villagers, bats were present there for last one month and reported when the bats came the pod production of Parkia is also become high. In another example a very few Parkia trees are available in the campus of Rain Forest Research Institute, Jorhat, Assam. They show pod formation at the age of 7-8 years even though formation of inflorescence is happens regularly and falls without any fruit formation. It may be due to declining of bats in abundance in the areas results in pollination failure of the species. As reported bats pollinating is a strategy which results in high levels of pollen transfer and thus enhances genetic diversity in plant populations reduces inbreeding depression and contributions of floral traits to plant fitness which should in turn affect the rates and directions of floral evolution. Since, there have been no detail studies on pollination of the Asian species under the genus it is utmost necessary to focus on the reported works on the subject.